Financialising acute kidney injury: from the practices of care to the numbers of improvement. Issue 5 (12th February 2019) - Bailey, Simon; Pierides, Dean; Brisley, Adam; Weisshaar, Clara; Blakeman, Thomas
Abstract: Although sociological studies of quality and safety have identified competing epistemologies in the attempt to measure and improve care, there are gaps in our understanding of how finance and accounting practices are being used to organise this field. This analysis draws on what others have elsewhere called 'financialisation' in order to explore the quantification of qualitatively complex care practices. We make our argument using ethnographic data of a quality improvement programme for acute kidney injury (AKI) in a publicly funded hospital in England. Our study is thus concerned with tracing the effects of financialisation in the emergence and assembly of AKI as an object of concern within the hospital. We describe three linked mechanisms through which this occurs: (1) representing and intervening in kidney care; (2) making caring practices count and (3) decision‐making using kidney numbers. Together these stages transform care practices first into risks and then from risks into costs. We argue that this calculative process reinforces a separation between practice and organisational decision‐making made on the basis of numbers. This elevates the status of numbers while diminishing the work of practitioners and managers. We conclude by signalling possible future avenues of research that can take up these processes.